Study of clinical effects of aspartame in sickle cell disease and sickle cell crisis - Gosavi, Rajesh V.; Aher, Mahesh U. (International Journal of Research in Medical Sciences, 2017)
Background: Sickle cell disease is the commonest heritable hematologic abnormality affecting humans and is highly prevalent in central India. Aspartame is the only agent that can prevent sickling tested in-vitro and in-vivo so far. With the available data being relatively scarce, this study aims to study the efficacy of aspartame in sickle cell crisis and sickle cell disease. Methods: Forty cases and controls each were selected as per predefined criteria. Controls were treated with standard therapy of analgesics, IV fluids, antibiotics and oxygen, if needed. Cases were treated with oral aspartame in addition to standard therapy. Clinical grading was done before respective treatment in both cases and controls and comparisons were drawn. Results: 78.9% cases and 66% controls were pain free at the end of 72 hours; with p-value of 0.093, which is statistically insignificant. 78.7% cases (n=33) and 64.4% controls (n=33) with SS pattern had grade 0 pain at the end of 72 hours, results being statistically insignificant. 81% cases (n=7) and 75% controls (n=7) with AS pattern had grade 0 pain at the end of 72 hours, which was similar in both groups with statistically insignificant p-value of 0.753. Conclusions: Oral Aspartame as an add-on therapy to standard therapy for vaso-occlusive crisis in sickle cell disease appears to have better response than standard therapy alone.